Hierarchical Porous Graphene-Iron Carbide Hybrid Derived From Functionalized Graphene-Based Metal-Organic Gel as Efficient Electrochemical Dopamine Sensor - Vermisoglou, Eleni C; Jakubec, Petr; Malina, Ondřej; Kupka, Vojtěch; Schneemann, Andreas; Fischer, Roland A; Zbořil, Radek; Jayaramulu, Kolleboyina; Otyepka, Michal (Frontiers in chemistry, 2020)
A metal-organic gel (MOG) similar in constitution to MIL-100 (Fe) but containing a lower connectivity ligand (5-aminoisophthalate) was integrated with an isophthalate functionalized graphene (IG). The IG acted as a structure-directing templating agent, which also induced conductivity of the material. The MOG@IG was pyrolyzed at 600°C to obtain MGH-600, a hybrid of Fe/Fe3C/FeOx enveloped by graphene. MGH-600 shows a hierarchical pore structure, with micropores of 1.1 nm and a mesopore distribution between 2 and 6 nm, and Brunauer-Emmett-Teller surface area amounts to 216 m2/g. Furthermore, the MGH-600 composite displays magnetic properties, with bulk saturation magnetization value of 130 emu/g at room temperature. The material coated on glassy carbon electrode can distinguish between molecules with the same oxidation potential, such as dopamine in presence of ascorbic acid and revealed a satisfactory limit of detection and limit of quantification (4.39 × 10-7 and 1.33 × 10-6 M, respectively) for the neurotransmitter dopamine.
Keywords: sensing; graphene; nanocomposite; gel; dopamine; metal–organic gel